Human resource audit in the academic libraries in Butuan City using the Philippine Association of Academic and Research Libraries (PAARL) standard - Estrella, Faith Anemone O.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
This thesis on Human Resource Audit on the Academic libraries in Butuan City is developed to look into the status of libraries in eight colleges. The study sought to know their qualifications and the training they have acquired to make them efficient librarians; to bring to the administration's awareness the problems and deficiencies faced by each of the libraries studied with regard to the human resources factors; to urge the administration to involve their librarians to participate in curriculum planning and other decision making that involves the library's role in the academic structure; and to urge these libraries to apply the proposed PAARL standard in their respective libraries.
The findings indicate that there are two college libraries (SJIT and UC) which have the largest number of personnel; only twelve librarians have either Bachelor of Science degree or have major in Library Science; there are sixteen librarians who have undergone various training programs since their appointments; there are five schools (ACF, BCC, BDC, SJIT, and UC) that satisfy the ratio between librarians and student required by PAARL; there are three school administrations (AIT, SJIT, and UC) which allow their librarians to participate in the curriculum planning process; only four libraries have written policies; only three libraries have organizational charts; none of the libraries under study is involved in any cooperative activities; and only one library (SJIT) knows about the proposed PAARL standards.
It is recommended that librarians should further undergo developmental training, should take part in curriculum planning process, should be given further professional responsibilities; and should engage in cooperative activities. Finally, they should apply the proposed PAARL standard in their libraries.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Libraries -- Philippines -- Mindanao -- Butuan City; Academic Libraries -- Philippines -- Mindanao -- Butuan City; Libraries -- Standards. -- Philippines